ANALISIS PRESTASI AKADEMIK PADA SEKOLAH DASAR NEGERI 20 KOTA LHOKSEUMAWE - Hendrawaty; Nailus Sakdah; Azhar (E-Jurnal Universitas Samudra, 2020)
SDN 20 Banda Sakti Pusong Baru is one of 81 elementary education institutions in the city of lhokseumawe. This school has administrative data, namely 531 students, 30 teachers, and 18 classes. Each student has value data, where the data is processed and stored in the Excel application. This is a problem because the Excel application is offline. When inputting data, sometimes data redundancy occurs between the Excel files that are processed, saving the Excel file is sometimes at risk of being lost or exposed to a virus. Teachers do not understand how to analyze data in the excel application so that schools cannot evaluate teacher and student performance. From these problems, a Data warehouse system was built at SDN 20 Banda Sakti Pusong Baru. The data warehouse is useful for managing administrative data and analyzing value data at the school. The data warehouse was built using the Nine Step Design Method. Analysis of the data warehouse built in graphical form. Data analysis for teacher and student evaluations based on PPDB online includes science, mathematics and Indonesian language subjects. The results of the graph analysis show that the decline in value that occurred in the odd semester 2019-2020 with a decrease in value of 79 for Science subjects, 80.3 for Mathematics subjects, and 80.8 for Indonesian subjects in class VI A so that schools can conduct an evaluation of teacher performance in that year.